1993
DOI: 10.1073/pnas.90.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenicity in simian virus 40-transformed 3T3 cells transfected with alpha-actinin cDNA.

Abstract: Human cytoskeletal a-actinin cDNA was transfected into highly malignant simian virus 40-transformed BALB/c 3T3 (SVT2) cells that express 6-fold lower levels of a-actinin than nontransformed BALB/c 3T3 cells. SVT2 clones expressing various levels of a-actinin were isolated and their structure and tumorigenic properties were determined. Transfected SVT2 clones expressing a-actinin at levels found in nontumorigenic 3T3 cells displayed a flatter phenotype, a decreased ability to grow in suspension culture in soft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
75
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(83 citation statements)
references
References 43 publications
8
75
0
Order By: Relevance
“…Candidate type II tumor suppressor genes such as NO3 (Ozaki and Sakiyama, 1994), maspin (Zou et al, 1994), ela®n (Zhang et al, 1995), a-actinin (Gluck et al, 1993), tropomyosin 1 and 2 (Prasad et al, 1993;Gimona et al, 1996) and SSeCKS (Lin and Gelman, 1997) have been isolated. Although none of their anti-tumor functions has been clari®ed yet, their de®nition as tumor suppressors is strengthened by at least two criteria (Lin and Gelman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate type II tumor suppressor genes such as NO3 (Ozaki and Sakiyama, 1994), maspin (Zou et al, 1994), ela®n (Zhang et al, 1995), a-actinin (Gluck et al, 1993), tropomyosin 1 and 2 (Prasad et al, 1993;Gimona et al, 1996) and SSeCKS (Lin and Gelman, 1997) have been isolated. Although none of their anti-tumor functions has been clari®ed yet, their de®nition as tumor suppressors is strengthened by at least two criteria (Lin and Gelman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in actin cytoskeleton in malignant cells have been found to be correlated with altered expression of various ABPs (Vandekerckhove et al, 1990;Button et al, 1995;Wang et al, 1996;Clark et al, 2000;Pawlak and Helfman, 2001). Experimental manipulations restoring the normal expression levels of several different types of ABPs have been successful in suppressing the phenotype of transformed cells (Gluck et al, 1993;Tanaka et al, 1995;Nikolopoulos et al, 2000), therefore implying that deregulation of ABPs directly contribute to oncogene-induced transformed phenotype of tumour cells. In the emerging story on the role of ABPs in cancer, profilin-1 (Pfn1 -a ubiquitously expressed G-actin-binding protein) is found to be expressed at a significantly low level in both human breast cancer tissue and a variety of breast carcinoma cell lines (Janke et al, 2000), pancreatic (Gronborg et al, 2006) and hepatic (Wu et al, 2006) carcinoma cells compared to their normal counterparts.…”
mentioning
confidence: 99%
“…Changes in the expression of a number of micro®lament-associated proteins during neoplastic transformation have been well documented (Button et al, 1995;Jammey and Chaponnier, 1995). For example, the expression of gelsolin (Vandekerckhove et al, 1990), vinculin (Ferna ndez et al, 1992), a-actinin (GluÈ ck et al, 1993) and tropomyosins (Leonardi et al, 1982;Cooper et al, 1985;Lin et al, 1985;Matsumura et al, 1983), which bind to and/or modulate the polymerization status of actin, is reported to be down regulated as the cells acquire malignant phenotype.…”
mentioning
confidence: 99%